2015
DOI: 10.1186/s12968-015-0176-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular volume quantification in isolated hypertension - changes at the detectable limits?

Abstract: BackgroundDiffuse myocardial fibrosis (DMF) is important in cardiovascular disease, however until recently could only be assessed by invasive biopsy. We hypothesised that DMF measured by T1 mapping is elevated in isolated systemic hypertension.MethodsIn a study of well-controlled hypertensive patients from a specialist tertiary centre, 46 hypertensive patients (median age 56, range 21 to 78, 52 % male) and 50 healthy volunteers (median age 45, range 28 to 69, 52 % male) underwent clinical CMR at 1.5 T with T1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
60
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 35 publications
9
60
2
2
Order By: Relevance
“…Этот метод является наиболее пригод-ным для выявления инфаркта миокарда, где различия между нормальным и пострадавшим миокардом более отчетливы. Определение внеклеточного объема может обнаружить ранние изменения, связанные с фиброзом, которые не всегда обнаруживают при исследовании с замедленным выведением гадолиния [19][20][21].…”
Section: диагностика фиброзаunclassified
“…Этот метод является наиболее пригод-ным для выявления инфаркта миокарда, где различия между нормальным и пострадавшим миокардом более отчетливы. Определение внеклеточного объема может обнаружить ранние изменения, связанные с фиброзом, которые не всегда обнаруживают при исследовании с замедленным выведением гадолиния [19][20][21].…”
Section: диагностика фиброзаunclassified
“…Since both have been proved to be associated with adverse clinical outcome in STEMI patients [27], these factors might also contribute to the increased risk of infarction patients with antecedent HTN. Recent studies could also disclose that diffuse myocardial fibrosis, measured by T1 mapping, is increased in patients with hypertension and previous infarction [28].…”
Section: Antecedent Hypertension Baseline Risk Profile and Clinical mentioning
confidence: 99%
“…Nevertheless, we cannot exclude early, diffuse myocardial tissue alterations under the detectable limits, similar to other recent findings in patients with arterial hypertension. 46 assessment in 20 asymptomatic, long-term CA involving resting ECG, exercise ECG, circulating biomarkers, echocardiography and advanced CMR techniques such as ECV imaging to detect diffuse myocardial injury. We found that asymptomatic CA had normal LV volumes, mass and function as well as normal circulating biomarkers compared with healthy volunteers.…”
Section: Data Given As N (%) or Median (Iqr) Abbreviations As Inmentioning
confidence: 99%